Volumetric Humeral Canal Fill Ratio Effects Primary Stability and Cortical Bone Loading in Short and Standard Stem Reverse Shoulder Arthroplasty: A Biomechanical and Computational Study - Daniel Ritter; Patric Raiss; Patrick J. Denard; Brian C. Werner; Peter E. Müller; Matthias Woiczinski; Coen A. Wijdicks; Samuel Bachmaier (Journal of Imaging)
Objective: This study evaluated the effect of three-dimensional (3D) volumetric humeral canal fill ratios (VFR) of reverse shoulder arthroplasty (RSA) short and standard stems on biomechanical stability and bone deformations in the proximal humerus. Methods: Forty cadaveric shoulder specimens were analyzed in a clinical computed tomography (CT) scanner allowing for segmentation of the humeral canal to calculate volumetric measures which were verified postoperatively with plain radiographs. Virtual implant positioning allowed for group assignment (VFR < 0.72): Standard stem with low (n = 10) and high (n = 10) filling ratios, a short stem with low (n = 10) and high filling ratios (n = 10). Biomechanical testing included cyclic loading of the native bone and the implanted humeral component. Optical recording allowed for spatial implant tracking and the quantification of cortical bone deformations in the proximal humerus. Results: Planned filling ratios based on 3D volumetric measures had a good-to-excellent correlation (ICC = 0.835; p < 0.001) with implanted filling ratios. Lower canal fill ratios resulted in significantly higher variability between short and standard stems regarding implant tilt (820 N: p = 0.030) and subsidence (220 N: p = 0.046, 520 N: p = 0.007 and 820 N: p = 0.005). Higher filling ratios resulted in significantly lower bone deformations in the medial calcar area compared to the native bone, while the bone deformations in lower filling ratios did not differ significantly (p > 0.177). Conclusions: Lower canal filling ratios maintain dynamic bone loading in the medial calcar of the humerus similar to the native situation in this biomechanical loading setup. Short stems implanted with a low filling ratio have an increased risk for implant tilt and subsidence compared to high filling ratios or standard stems.